Construction innovation and process improvement - Akintoye, Akintola; Goulding, Jack.; Zawdie, Girma, 1946-; ProQuest (Firm) (Chichester [England] ; Ames, Iowa : Wiley-Blackwell, 2012)
"This book sets out the innovative practices that have been introduced from other industries and shows how the construction industry has learnt from these. It explores the commercial significance of innovation; outlines its role in transforming practice and improving competitiveness; and lists technological and market forces driving the innovation process. The authors explain why some attempts at innovation in construction fail and others succeed and detail the management of change, outlining economic, technical and organisational characteristics which may inhibit change in practice as well as examine management strategies for making change happen"--
Machine generated contents note: Chapter 1 Introduction: Learning from other industries.Chapter 2 Innovation and changes in industrial practice.Chapter 3 Management of Change.Chapter 4 Lean production.Chapter 5 Integrated manufacturing.Chapter 6 Concurrent Engineering.Chapter 7 Materials requirements planning.Chapter 8 Just-in-Time manufacturing.Chapter 9 Supply chain management.Chapter 10 Knowledge management applications.Chapter 11 Quick response systems - Agile manufacturing.Chapter 12 Electronic data interchange.Chapter 13 Radio Frequency Identification Devices.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Construction industry -- Technological innovations; Civil engineering -- Technological innovations; Competition; Electronic books